Penerapan Aplikasi Penerimaan Siswa Baru di Sekolah Menengah Kejuruan Berbasis Android Menerapkan Model Waterfall - Triyana Sugiyarti; Qadhli Jafar Adrian (Journal of Information System Research (JOSH), 2025)
New Student Admission (PSB) is an important activity in the education system that requires an effective and efficient process. YP 17 Baradatu High School, located in Way Kanan Regency, still uses manual methods in the PSB process, which causes many obstacles such as data input errors, delays and difficulties in managing information. Therefore, this research aims to develop an Android-based New Student Admissions application that can simplify the PSB process in the school, by applying the Waterfall software development model. The Waterfall model was chosen as a development method because of its systematic and sequential nature, which is suitable for projects that have clear and fixed needs. This application is expected to be able to automate the entire PSB process, starting from registration, data verification, announcement of selection results, to managing new student data in an integrated and efficient manner. In this research, the solution provided is an Android-based mobile application that allows prospective students and schools to access and manage PSB data more practically. The main objective of this research is to design and implement an Android-based PSB application that can increase the effectiveness and efficiency of the new student admission process at SMA YP 17 Baradatu. With this application, it is hoped that it can reduce errors in data management, speed up the admission process, and make it easier for prospective students to register online. The contribution of this research is the development of an Android-based PSB application that can be adapted by other schools that face similar problems. The interim results achieved show that this application has succeeded in simplifying the registration process and facilitating communication between prospective students and the school. Initial testing of the application also showed a positive response from users regarding the ease of use and functionality of the application in supporting the new student admissions process.